GROWTH OF OPTICAL GRADE GERMANIUM CRYSTALS - Waris, M.; J. Akhtar, S. M.; Mehmood, N.; Ashraf, M.; Siddique, M. (The Nucleus, 2010)
A novel design of Czochralski( CZ ) growth station in a low frequency induction furnace is described and growth of optical grade Ge crystal as a test material is performed achieving a flat solid –liquid interface shape. Grown Ge crystals are annealed in air at 450 -500 °C for 4 hrs and then characterized by determination of crystallographic orientation by Laue (back-reflection of X-rays) method, dislocation density studies by etch-pits formation, measuring electrical resistivity by 4-probe technique, conductivity type determination by hot probe method, measurement of hardness on Moh’s scale and optical transmission measurement in IR region. The results obtained are compared to those reported in the literature. The use of this growth station for other materials is suggested.